Pengaruh Penambahan Abu Bonggol Jagung Pada Tanah Lempung Terhadap Uji California Bearing Ratio - Orlinianto Pasauran; Irwan Lie Keng Wong; Monika D.M Palinggi (Paulus Civil Engineering Journal, 2020)
The methodology in this study is to conduct a series of soil characteristic testing and then design the composition of the Proctor Standard testing mixture to obtain optimum moisture content values, California Bearing Ratio (Unsoaked Design CBR and Soaked Design CBR) to obtain soil support value. The results of the research showed that the soil meets the characteristics of clay soil. From standard compaction testing at point 1 and point 2 with mixed variations of 0%, 2.5%, 5%, 7.5%, 10% experienced an increase in optimum water content and maximum dry density. Corn weevil ash increases the value of CBR soil so that it can be used to increase the carrying capacity of organic clay soil.